Nanodiamonds Applications in Biology and Nanoscale Medicine - Ho, Dean (Springer US : Imprint: Springer, 2010)
Nanodiamonds: Applications in Biology and Nanoscale Medicine highlights how nanodiamonds have emerged in clinical and medical relevance through assisting in the processes of drug delivery, cellular interrogation and detection, among others. This book collects the work of internationally-recognized experts in order to give the reader a view of nanodiamonds' vast potential as a useful platform in scientific, engineering and clinical communities. Editor Dean Ho uses his many years of experience working with nanodiamonds to show how the transcendent potential of nanodiamonds, while also: Including contributions from clinical scientists, experts in carbon-based drug delivery and materials researchers. Highlighting a paradigm shift in translational applications of novel materials like nanodiamonds in medicine. Providing in-depth insight into biological responses to nanodiamond exposure. Nanodiamonds: Applications in Biology and Nanoscale Medicine is a must-read for anyone working in the fields of biomedicine, nanotechnology or biochemistry, and will also appeal to any researchers or engineers with an interest in these fields. .